Sexual dimorphism in digit length ratios of the second to fourth digits (2D:4D) in two species of green toads (Pelobates syriacus Boettger, 1889 and Bufo viridis (Laurenti, 1768)) - Iman Alinezhadi; Nastaran Heidari; Hossein Javanbakht (یافته‌های نوین در علوم زیستی, 2020)
Sexual dimorphism in the ratio of digits length is a morphological feature resulted from the interaction between sex hormones and prenatal Hox genes, the latter is known to control the development of both limbs and genitals. The status of this trend and ratios have been investigated in various animal groups, including humans, other mammals, birds, reptiles, and amphibians. In this study, the body length and sexual dimorphism in the second-to-fourth, second-to-third and third-to-fourth digit lengths ratios (i.e., 2D:3D, 2D:4D, 3D:4D) of left fore and hind limbs were investigated in 54 specimens of toads collected from the northern Iran, including Bufo viridis (16 males and 19 females) and Pelobates syriacus (10 males and 9 females). In addition, the body length of the studied specimens were recorded. The results showed that the average body length (SVL) of female individuals of Pelobates syriacus was higher than those in males, which was found to be statistically significant (P≤0.05). Meanwhile, the average body length (SVL) of female individuals of Bufo viridis was found to be higher than those in males, however, the difference was not statistically significant. No sexual dimorphism was detected in the second-to-fourth, second-to-third and third-to-fourth digit lengths ratios of left fore and hind limbs between the male and female undividuals of Bufo viridis. However, the second-to-fourth digit ratio (2D:4D) in Pelobates syriacus species were found to be significantly different (P=0.040) between the male and female individuals, as the ratio was higher in males than females. Therefore, it could be concluded that the sexual dimorphism in 2D:4D of Pelobates syriacus species is consistent with those in most amphibians and diapsids.